2018
DOI: 10.1001/jamainternmed.2017.8650
|View full text |Cite
|
Sign up to set email alerts
|

Association of Ontario’s Ban on Menthol Cigarettes With Smoking Behavior 1 Month After Implementation

Abstract: Drs Lee and Fitchett had full access to all of the data in the study and take responsibility for the integrity of the data and the accuracy of the data analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
55
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 8 publications
6
55
1
Order By: Relevance
“…Consistent with other data from the USA (Dutra and Glantz 2017;Levy et al 2018), it appears as though the increase in youth e-cigarette use has not led to an increase in youth smoking. The availability of flavours of e-cigarettes may have increased their appeal over traditional cigarettes (Zhu et al 2014); for example, within Ontario as of January 1, 2017, menthol-flavoured cigarettes were banned (Chaiton et al 2018), leaving e-cigarettes as one of the few a Ever use of e-cigarettes was not assessed prior to 2015; non-current users include those who have never used e-cigarettes and those who did not use e-cigarettes in the last 30 days b Students who identified as "off-reserve Aboriginal" are also included in this category flavoured tobacco products available. Other evidence suggests that promotion on social media may have also contributed to the increased appeal of e-cigarettes over traditional cigarettes (Allem et al 2018;Laestadius et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with other data from the USA (Dutra and Glantz 2017;Levy et al 2018), it appears as though the increase in youth e-cigarette use has not led to an increase in youth smoking. The availability of flavours of e-cigarettes may have increased their appeal over traditional cigarettes (Zhu et al 2014); for example, within Ontario as of January 1, 2017, menthol-flavoured cigarettes were banned (Chaiton et al 2018), leaving e-cigarettes as one of the few a Ever use of e-cigarettes was not assessed prior to 2015; non-current users include those who have never used e-cigarettes and those who did not use e-cigarettes in the last 30 days b Students who identified as "off-reserve Aboriginal" are also included in this category flavoured tobacco products available. Other evidence suggests that promotion on social media may have also contributed to the increased appeal of e-cigarettes over traditional cigarettes (Allem et al 2018;Laestadius et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Chaiton et al [17,18], conducted two studies analyzing the impact of the 2017 Ontario, Canada ban on menthol cigarettes. Both studies used random-digit dialing to identify a sample of smokers aged 16 and older prior to the menthol ban's implementation.…”
Section: Individual Behaviormentioning
confidence: 99%
“…Both studies used random-digit dialing to identify a sample of smokers aged 16 and older prior to the menthol ban's implementation. The first study, with 324 smokers at one-month post-ban [18], found that 28% of menthol smokers switched to non-menthol cigarettes, 29% attempted to quit, and 29% used an alternative flavored tobacco or e-cigarette product. A second study [17] conducted one-year post-ban with a sample of 913 smokers (including non-menthol and menthol users) found that 56% of all smokers had made at least one quit attempt, and 19% reported no current tobacco use.…”
Section: Individual Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…Before the ban 14% thought they would quit smoking and, 1 month post-ban, 29% reported having quit. 20 A later Ontario study found that daily menthol smokers, compared with non-menthol smokers, were significantly more likely to self-report quitting 1 year after the ban. 21 There are no reports concerning how menthol bans may affect smoking among persons with substance use or mental health problems, but there is reason to think they may respond differently from general population smokers.…”
Section: Introductionmentioning
confidence: 98%